Digital Transformation : An Analysis of the Implementation of Civil Registration Information Systems (SIAK) in Local Governments - Hamdi, Rizal; Hidayatullah, Rahmat; Khumayah, Siti; Rahmayanti, Rahmayanti (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study intended to assess the efficacy and obstacles of SIAK implementation in Majalengka Regency to improve the quality of public services. The applied method is a descriptive qualitative approach with the Design-Reality Gap Model (ITPOSMO). The findings show that SIAK has not yet been fully implemented because of various reasons in terms of technological capability, staff competencies and managerial linkup. Little information is given on quality of services, and resources are scarce. In summary, SIAK has the ability to help improve efficiency, but it has not been fully reached with its intended perfect design.